Gleanings from the Field: Food Security, Resilience, and Experiential Learning (Lever Press, 2025)
In recent years, the concept of “food security” has garnered significant attention among policymakers, activists, and educators. Stemming from a growing awareness of the complexities surrounding access to sufficient food globally, movements advocating for food justice and sovereignty have emerged in response to these systemic inequities and health disparities, particularly in local communities. With the COVID-19 pandemic, conflicts in regions such as Ukraine and Gaza, and the escalating impacts of climate change, reliable food security has become exacerbated by these existing disparities. Gleanings from the Field argues that addressing food security is essential for tackling broader sustainability challenges facing humanity and recognizes the role of food in community-building, cultural exchange, and quality of life. However, promoting food security entails navigating intricate trade-offs, such as balancing economic interests in food supply with environmental concerns. This timely essay collection frames our food security challenges as “wicked problems,” puzzles without clear solutions that are characterized by evolving complexities and divergent stakeholder priorities. In classroom settings, they argue for the usage of experiential learning to cultivate “wicked problem-solving skills” among students. Gleanings from the Field exemplifies this approach, offering pedagogical interventions to prepare students for tackling these wicked problems, while advocating for high-impact learning experiences that enable students to grapple with the interconnected systems influencing food security. Through hands-on experiences and reflective practice, students gain a deeper understanding of these systems and their societal implications. Importantly, the contributions outlined in this volume underscore the need for a multidimensional view of food security, thus examining the intersections of economic interests, government policies, and social movements. By contextualizing food security within broader political-economic arrangements, educators can empower students to enact meaningful change. Gleanings from the Field argues for a holistic approach to food security education, one that acknowledges the fraught nature of wicked problems and equips students with the skills and knowledge needed for effective action. By integrating experiential learning, conceptual frameworks about food security and resilience, and real-world engagement, educators can cultivate a new generation of resilient problem-solvers committed to addressing food insecurity and other wicked problems.